Advancement of Scaffold-Based 3D Cellular Models in Cancer Tissue Engineering: An Update - Unnikrishnan, Kavitha; Thomas, Lynda Velutheril; Ram Kumar, Ram Mohan (Frontiers in Oncology, 2021)
The lack of traditional cancer treatments has resulted in an increased need for new clinical techniques. Standard two-dimensional (2D) models used to validate drug efficacy and screening have a low in vitro-in vivo translation potential. It is essential to recreate the in vivo tumour microenvironment at the three-dimensional (3D) level to resolve these limitations in the 2D culture and improve therapy results. The physical and mechanical environments of 3D culture allow cancer cells to expand in a heterogeneous manner, adopt different phenotypes, gene and protein profiles, and develop metastatic potential and drug resistance similar to human tumours. The current application of 3D scaffold culture systems based on synthetic polymers or selected extracellular matrix components promotes signalling, survival, and cancer cell proliferation. This review will focus on the recent advancement of numerous 3D-based scaffold models for cancer tissue engineering, which will increase the predictive ability of preclinical studies and significantly improve the clinical translation.